FORMALDEGID–KETON KONDENSATSIYASI ASOSIDA KOMPOZIT MATERIALLAR OLISH - To‘htaboyeva Muhayyo Maxfurali qizi; M. A. Ahmadaliyev (TADQIQOTLAR, 2026)
Abstract: Formaldehyde–ketone condensation reactions play an important role in  the  synthesis  of  polymeric  and  composite  materials  with  improved  mechanical, thermal, and chemical properties. This study investigates the formation of composite materials based on formaldehyde–ketone condensation products, focusing on reaction mechanisms,  synthesis  conditions,  and  material  characteristics.  The  obtained composites  demonstrate  enhanced  strength,  thermal  stability,  and  resistance  to chemical agents, making them suitable for application in construction, coatings, and industrial  materials.  The  results  confirm  that  controlling  reaction  parameters significantly affects the structure and performance of the resulting composites.